2020
DOI: 10.1038/s41598-020-57899-7
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical analyses and experimental validation of the effects caused by the fluorinated substituent modification of DNA

Abstract: Halogen-modified nucleic acid molecules, such as trifluorothymidine (FTD) and 5-fluorouracil, are widely used in medical science and clinical site. These compounds have a very similar nucleobase structure. It is reported that both of these compounds could be incorporated into DNA. The incorporation of FTD produces highly anti-tumor effect. However, it is not known whether to occur a significant effect by the incorporation of 5-fluorouracil. Nobody knows why such a difference will occur. To understand the reaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…3B. Based on our previous theoretical predictions 16 , we validated the sequences with FTD substitutions at thymidine positions adjacent to electron-rich bases (Fig. 3C).…”
Section: ) Antitumor Drug and Test Sequences Used For Veri Cationsmentioning
confidence: 64%
See 1 more Smart Citation
“…3B. Based on our previous theoretical predictions 16 , we validated the sequences with FTD substitutions at thymidine positions adjacent to electron-rich bases (Fig. 3C).…”
Section: ) Antitumor Drug and Test Sequences Used For Veri Cationsmentioning
confidence: 64%
“…From our previous study, as shown in Fig. 2B, it is presumed that thymidine adjacent to adenine and guanine having a part of electron rich structure is likely to replace FTD in DNA replication 16 . This is because the uorine atoms at the tri uoromethyl group cause an attractive interaction with an electron-rich molecular orbital via a halogen bonding.…”
Section: ) Antitumor Drug and Test Sequences Used For Veri Cationsmentioning
confidence: 84%
“…Methylation at the O 4 ‐position for the CF 3 dU ‐ O 4 Me containing duplex reduced stability by approximately 10 °C, with a value slightly less than that observed for the C5‐halogenated series. It has been reported that the presence of C5‐trifluoromethyl‐2′‐deoxyuridine in DNA might affect its hydrogen‐bond properties thus influencing CF 3 dU :dA base pairing complementarity due to dispersion forces as well as altering interactions with neighboring bases [36] . Overall, for this series of halogens and trifluoromethyl group at the C5 position for the O 4 ‐methyl analogs, a minimal effect on the reduction of DNA duplex stability compared to T was observed [28] …”
Section: Resultsmentioning
confidence: 84%